2016
DOI: 10.18632/oncotarget.10075
|View full text |Cite
|
Sign up to set email alerts
|

A novel capsid-modified oncolytic recombinant adenovirus type 5 for tumor-targeting gene therapy by intravenous route

Abstract: Oncolytic adenovirus (Ad)-vectored gene therapy is a promising strategy for cancer treatment. However, the lack of cancer cell selectivity or tumor tissue specificity of Ads limits their clinical application by intravenous (IV) injection. In this paper, a novel recombinant Ad5 vector was constructed carrying the capsid protein IX modified by the tumor necrosis factor related apoptosis-inducing ligand (TRAIL), which targets tumor cells bearing high levels of its receptor far above those of normal cells. Specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 51 publications
0
19
0
Order By: Relevance
“…16,17 A4 showed significant tumor-targeting capability, reduced liver tropism, and potent antitumor activity. 15 However, we also found that the amount of TRAIL coupled with the capsid protein on the viral particle surface was less than expected, indicating that A4 needs to be further improved to ensure better efficacy. Previous studies showed that gene therapy based on either recombinant soluble TRAIL (sTRAIL) or native TRAIL showed selective cytotoxicity toward cancer cells.…”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations
“…16,17 A4 showed significant tumor-targeting capability, reduced liver tropism, and potent antitumor activity. 15 However, we also found that the amount of TRAIL coupled with the capsid protein on the viral particle surface was less than expected, indicating that A4 needs to be further improved to ensure better efficacy. Previous studies showed that gene therapy based on either recombinant soluble TRAIL (sTRAIL) or native TRAIL showed selective cytotoxicity toward cancer cells.…”
Section: Introductionmentioning
confidence: 72%
“…Although A4 showed good targeting and antitumor activity in TRAIL-sensitive breast cancer cells, we found that only~17% of pIX was linked to TRAIL. 15 To enhance AML cell targeting and killing efficacy, we used a new strategy that involved expressing sTRAIL fused to the zipper protein in E. coli, which was termed zTN. Then, zTN was incubated with A4 at 4°C for 16 h. The zTN-coated A4 (named zA4) was purified by density gradient centrifugation (Fig.…”
Section: Generation Of Trail-coated Oncolytic Adenovirusmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, protein IX (pIX) exposed on the adenoviral capsid also represents an ideal site for insertion of a tumor-targeting ligand at its C terminus [21,22]. In our previous study, we constructed a novel tumor necrosis factor-related apoptosis-inducing ligand (TRAIL)-modified oncolytic adenovirus vector, termed A4 [23]. The engineered A4 virus carried the TRAIL gene in its genome and presented the TRAIL protein on the viral surface via a Leu-zipper linkage to pIX [23].…”
Section: Ivyspringmentioning
confidence: 99%
“…In our previous study, we constructed a novel tumor necrosis factor-related apoptosis-inducing ligand (TRAIL)-modified oncolytic adenovirus vector, termed A4 [23]. The engineered A4 virus carried the TRAIL gene in its genome and presented the TRAIL protein on the viral surface via a Leu-zipper linkage to pIX [23]. TRAIL, a typical member of the TNF superfamily, has been demonstrated in numerous studies to specifically induce cancer cell apoptosis by binding to its receptor, TRAILR1 (also known as DR4) or TRAILR2 (also known as DR5), which contain intracellular death domains [24,25].…”
Section: Ivyspringmentioning
confidence: 99%